Implementation Of Extreme Learning Machine Method With GVF Snake For Character Recognition: Implementation Of Extreme Learning Machine Method With GVF Snake For Character Recognition - Pradana Yusna; Yennimar Yennimar (Institute of Computer Science (IOCS), 2020)
In everyday life, sometimes it is necessary to change the contents of the printouts of certain documents, but the digital files from the printed documents have been lost. Retype the document manually will certainly spend a lot of time making it inefficient. To solve this problem, the printed document can be scanned into a digital image file and a character recognition system is implemented to recognize the characters contained therein. In this study, the Gradient Vector Flow Snake (GVF Snake) method is used to determine the boundaries of an object based on the computed vector gradient in the form of binary or gray-level values ??obtained from an image with several frameworks. After that, the Extreme Learning Machine (ELM) method will be used to predict the characters that have been broken up by the GVF Snake method. The results of this study are software that applies the GVF Snake and ELM methods to perform the character recognition process of an image printed by a document.